137k views
2 votes
Convert y = x2 - 4x + 1 to vertex form by completing the square.

O y= (- 1)2 + 4
O y= (1 - 2)2 +5
O y= (x - 2)2 – 3
O y = (x - 4) + 1

User Matt Hulse
by
4.9k points

2 Answers

2 votes

Answer:

y = (x - 2)² - 3

Explanation:

Given

y = x² - 4x + 1

To complete the square

add/subtract ( half the coefficient of the x- term )² to x² - 4x

y = x² + 2(- 2)x + 4 - 4 + 1

= (x - 2)² - 3

User Targnation
by
4.9k points
5 votes

Answer:

vertex: (-2, -3)

Explanation:

y = x2 + 4x + 1

y = x2 + 4x + 22 + 1 - 22

y = (x + 2)2 + 1 - 4

y = (x + 2)2 - 3 in y = (x - h)2 + k, (h, k) is the vertex.

User Hxin
by
4.8k points